Building and integrating virtual private networks with Openswan : learn from the developers of Openswan how to building industry-standard, military-grade VPNs and connect them with Windows, Mac OS X, and other VPN vendors /: learn from the developers of Openswan how to building industry-standard, military-grade VPNs and connect them with Windows, Mac OS X, and other VPN vendors. (©2006) - Unknown
No abstract available